HUBUNGAN PENGANGGURAN DENGAN TINGKAT KEMISKINAN MASYARAKAT - Dira Nurhikmah; Hendra Riofita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Unemployment and poverty are major issues in economic development that are closely interrelated and have a broad impact on societal welfare. This study aims to analyze the relationship between unemployment and poverty levels as well as the factors influencing them. The method used is a descriptive qualitative approach through literature study from various scientific sources such as books, journals, and official reports. The results show that unemployment has a significant effect on increasing poverty, both directly through loss of income and indirectly through reduced purchasing power, limited access to education, and social inequality. In addition, external factors such as economic crises and globalization also strengthen this relationship. Therefore, comprehensive and sustainable policies are needed to reduce unemployment and poverty.